2022
DOI: 10.1155/2022/8122568
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] Securitization Concept and Its Application to Environmental Problems in the Kurdistan Region: Prospects and Obstacles

Abstract: Environmental pollution has caused a wide range of problems across the globe. Various studies have focused on worldwide water and environmental issues and their effects on human health and political and social aspects. This article, on the other hand, discusses soil, water, and air pollution as well as the overuse of water resources. This study then discusses these problems as a security issue in the Kurdistan Region of Iraq (KRI) context. This research adopts a qualitative approach. It reviews the results of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…Journal of Environmental and Public Health has retracted the article titled "Securitization Concept and Its Application to Environmental Problems in the Kurdistan Region: Prospects and Obstacles" [1] due to concerns that the peer review process has been compromised. Following an investigation conducted by the Hindawi Research Integrity team [2], signifcant concerns were identifed with the peer reviewers assigned to this article; the investigation has concluded that the peer review process was compromised.…”
mentioning
confidence: 99%
“…Journal of Environmental and Public Health has retracted the article titled "Securitization Concept and Its Application to Environmental Problems in the Kurdistan Region: Prospects and Obstacles" [1] due to concerns that the peer review process has been compromised. Following an investigation conducted by the Hindawi Research Integrity team [2], signifcant concerns were identifed with the peer reviewers assigned to this article; the investigation has concluded that the peer review process was compromised.…”
mentioning
confidence: 99%